Forage Yield of Sorghum under Water Deficit and Foliar Application of Zinc Sulphate and Salicylic Acid - Roya Karimi; Hashem Hadi; Mehdi Tajbakhsh (Journal of Agricultural Science and Sustainable Production, 2016)
The effect of foliar application of zinc sulphate and salicylic acid on forage yield and some qualitative and physiological characteristics of sorghum bicolor Var. Speedfeed, under water deficit conditions, was studied as split-plot experiment based on randomized complete block design with three replications at University of Urmia Research Farm in 2013. Water deficit stress as main plot consisted of three levels (irrigation at the 90%, 70% and 50% of soil field capacity) and foliar applications as sub plot with five levels including: no foliar application (control), foliar application of salicylic acid (0.5 and 1mM) and zinc sulphate (300 and 3000 mg.l-1) Which were applied in the 5 to 6 leaf stage. The highest digestibility (64.76 %) was obtained from the foliar application of zinc sulphate 3000 mg.l-1 at all levels of water deficit. Maximum crude protein and ash contents (13.35% and 8.32%) were achieved with foliar application of zinc sulphate 3000 mg.l-1 in control and moderate water deficit. Severe water deficit decreased hay yield by 21.11% in comparison with control. Both foliar application of zinc sulphate 3000 mg/l and salicylic acid 0.5 mM with average of 1571.53 g.m-2 produced the highest hay yield. Therefore, these treatments that led to significant improvements in the hay yield quality and quantity are recommended as the best treatments of this research for farmers.